The creators of Port Arthur: Military engineers and A. I. von Gogen - Ivanova, Alina (project baikal, 2023)
The article presents the interim results of a study conducted within the framework of the scientific project “Architects and engineers of the eastern outskirts of Russia (second half of the 19th – early 20th centuries)”. The first part of the article is devoted to the military engineers of Port Arthur (K. I. Dubitsky, F. K. Avellan, A. A. Verse, F. D. Butler, L.L. Zatursky, I. A. Zaborovsky, Dobrov). The projects revealed in archival funds are published for the first time. The second part, which is written on the basis of publications in professional periodicals of the early 20th century, examines the role of A. I. von Gogen in designing the general plan of the New City and facilities of paramount importance for Port Arthur. The final part presents the foreign contemporaries’ opinion on the implementation of the plan of the city of Dalny.
Keywords: Port Arthur; military engineers; A. I. von Gogen